1992
DOI: 10.2307/3350085
|View full text |Cite
|
Sign up to set email alerts
|

Risky Business: Setting Public Health Policy for HIV-Infected Health Care Professionals

Abstract: An analysis of the restrictive proposals provoked by the case of Kimberly Bergalis and four other patients apparently infected with HIV during the course of dental treatment reveals that they resulted from an inability to evaluate appropriately the infinitesimal risk of HIV transmission from practitioner to patient. The proposals also resulted from an effort to create risk prevention policy without appreciating the distinction between regulating things or procedures, which have no human rights, and regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Such intervention studies might also be beneficial in the health domain. As previously discussed, Glantz et al (1992) showed that fear leads to unjustified discrimination against those with HIV infection. Teaching mental contrasting as a meta-cognitive strategy might thus help health care providers, relatives, and friends of HIV patients to overcome their unjustified fears about HIV infection.…”
Section: Applied Implicationsmentioning
confidence: 83%
See 1 more Smart Citation
“…Such intervention studies might also be beneficial in the health domain. As previously discussed, Glantz et al (1992) showed that fear leads to unjustified discrimination against those with HIV infection. Teaching mental contrasting as a meta-cognitive strategy might thus help health care providers, relatives, and friends of HIV patients to overcome their unjustified fears about HIV infection.…”
Section: Applied Implicationsmentioning
confidence: 83%
“…Gaines and Reed (1995), as well as Corenblum and Stephan (2001), showed that prejudicial hostility led to unfounded fears of negative future interactions between members of different races, religions, and ethnicities. Another domain of previously studied unjustified fear is in the realm of HIV infection (Glantz, Mariner, & Annas, 1992), wherein it was shown that HIV-infected medical praciitioners may be barred from practicing due to policy decisions based on fear rather than actual risk.…”
Section: Discussionmentioning
confidence: 99%
“…What is clear is that the burden of proof that individuals pose a threat to the public should be more demanding when the consequences of regulation include detention than when economic encumbrances are created 14. Furthermore, we need to recognise that, when people feel threatened, they focus inappropriately on external sources such as stereotyped minorities and blame them, rather than assessing other threats which are perhaps closer to home 15…”
mentioning
confidence: 99%
“…The American Medical Association has issued guidance that HIV-infected practitioners undertaking exposure-prone procedures must either disclose this to their patients, obtaining their informed consent prior to treatment or must withdraw from treatment. 15 16 The New York State Department of Health issued contradictory guidance which did not require disclosure because of the very low risk of transmission of HIV. Similar statements have been made by other American medical authorities.…”
Section: Reasons For Informing Patientsmentioning
confidence: 99%